The Existence of Customary Land Law of the Sultanate of Ternate After the Supreme Court Decision Number 57k/PDT/2017 - Aprizal Midu; Husen Alting; Suwarti Suwarti (Journal of Social Science)
This study aims to analyze the existence of customary land law of the sultanate of Ternate before and after the Supreme Court Decision Number 57K/PDT/2017. Meanwhile, legal efforts to resolve customary land disputes of the Sultanate of Ternate after the enactment of Supreme Court Decision Number 57K/PDT/2017 provide benefits to the Regional Government or customary law communities. This type of research uses Empirical Juridical research, that is, this research in addition to using scientific methods also sees the reality in the field. Especially regarding the Legal Existence of Customary Land of the Sultanate of Ternate After the Supreme Court Decision Number 57k/Pdt/2017. Empirical Legal Research or field research is a method to obtain data directly from the Sultanate of Ternate as well as from the family of the Sultanate of Ternate and related Regional Governments. The results showed that the existence of customary land law of the sultanate of Ternate before and after the Supreme Court Decision Number 57K/PDT/2017. Prior to the enactment of Law Number 5 of 1960 concerning Land Principal (UUPA) and the Supreme Court Decision Number 57K/PDT/2017. Permanent rights consist of; Aha Kolano (sultan's right), Aha Soa (clan right), Aha Cocatu (individual right). Meanwhile, temporary rights consist of; Tolagumi Rights (Right to Avoid Bala), Safa Rights, Ruba Banga Rights (Demolishing Forests), and Jurame Rights, or one's right to a piece of land that has been cultivated. The polemic over land ownership at the location of the Jiko Malamo beach tourist attraction, West Ternate District emerged after the Supreme Court Decision Number 57K / PDT / 2017 over the Jiko Malamo land dispute lawsuit between Hamiru Haruna (Plaintiff) and Hamzah Kalepa (Defendant) has now become state-owned land. Settlement of Customary Land Disputes of the Sultanate of Ternate After the enactment of Supreme Court Decision Number 57K/PDT/2017 provides benefits to local governments, which should be on lands in the territory of the Sultanate of Ternate must first pay attention to the subject of these lands. Subjects who control the land according to swaparaja land law can be divided into 3 (three), namely the Sultan (Kolano), soa, and Individuals / legal entities. Lands controlled by individuals give civil authority to those who control them.